Suggested methods for enhancement of aquaculture in the Southern Marshes of Iraq - Salman, Nadir A. (Iraqi Journal of Aquaculture, 2022)
Aquaculture activities in the southern part of Iraq faced many problems. Local people are not well aware that aquaculture could be a good activity to improve their socioeconomic status. There are very few hatcheries to supply enough fingerlings. The water quality is changing and becoming more saline, which have negative impact on the growth rate of the cultured freshwater species. To improve aquaculture in the southern part of Iraq, all these parameters should be considered to plan an effective management. Making use of the naturally-occurred water impoundments in the southern marshes and turning them into productive fish ponds is a practical approach. The present study suggests various rearing techniques which are suitable for such water bodies. These include introduction of peripheral and transaction dikes to create extensive fish ponds. Fish cages and net enclosures represent also special profitable approaches. Rearing fish in fish rice fields can also be practiced in certain areas in the marshlands. Conducting steps, implementation techniques and advantages of various rearing methods have been discussed. Fry and fingerlings supply should be maintained through establishing local hatcheries, which produce fingerlings of all carp species (common, grass and silver carp) in addition to some native species such as Bunni (B. sharpey). Aquaculture activities in the marshes should include releasing fingerlings into the available open waters using big net enclosures. Few other developmental recommendations were also suggested, such as the introduction of new fish species that are more tolerable to the present water quality. The introduction of new types of culture methods such as cages and recirculation systems which are compatible with the freshwater shortage, quality and depths. There are big chances of success especially with the availability of sufficient amount of very productive water and cheap work power, but research for optimizing stocking and harvesting is essential.